Value of renal vascular doppler sonography in cardiorenal syndrome type 1 - Çakal, Beytullah; Özcan, Özgür Ulaş; Omaygenç, Mehmet Onur; Karaca, İbrahim Oğuz; Kızılırmak, Filiz; Güneş, Hacı Murat; Boztosun, Bilal (Wiley, 2021)
Objectives Worsening of renal function in a patient with acute decompensated heart failure is called cardiorenal syndrome (CRS) type 1. Recent studies have shown an association of persistent systemic venous congestion with renal dysfunction. This trial was set up to investigate the changes of renal Doppler parameters with diuretic therapy in patients with CRS type 1. Methods Cases of CRS type 1 were identified among patients hospitalized for decompensated heart failure. Serial measurements of the renal venous impedance index (VII) and arterial resistive index (ARI) were calculated by pulsed wave Doppler sonography. Results A total of 30 patients who had creatinine improvement with diuresis (group 1) and 34 patients without any improvement (group 2) were analyzed. Patients in group 1 had higher median VII and ARI (VII, 0.86 versus 0.66;P < .001; ARI, 0.78 versus 0.65;P < .001) on admission. A high ARI on admission (odds ratio, 6.25; 95% confidence interval, 1.84-14.3;P= .003) predicted the improvement of serum creatinine levels with diuretic therapy independent of confounding factors in patients with CRS type 1. Conclusions Renal vascular Doppler parameters might offer guidance on the diagnostic and therapeutic strategies in prescribing decongestive therapy for decompensated heart failure.
Keywords: Decompensated Heart Failure; Diuretics; Renal Resistive Index; Venous Impedance Index